Pola Komunikasi dalam Komunitas Pendidikan - Budi Santoso (Nur Science Institute, 2021)
This research aims to find communication patterns in the educational community. Communication is a means of relationship between members of the education community, namely students, teachers, parents and stakeholders. This research uses a qualitative approach with literature review methods. Literature review or literature review is a term that is often done by learners while working on the final task. Lecturers and researchers are also fluent in using this term because the life of academics is very close to the behavior of literature review. Literature review will be conducted when you want to start to understand a new research topic, follow new research trends and understand the state-of-the-art of a research topic. Literature review not only means reading literature, but rather toward an in-depth and critical evaluation of previous research on a topic. A good literature review is one that evaluates the quality and new findings of a scientific paper. The intrinsic complexity of educational action, the role played by the habits of each actor involved, the lack of training of the latter for collaboration, the socio-cultural framework within which meetings take place, make relationships difficult. The role of parents in school life is increasingly important, transforming themselves from mere participation to authentic cooperation in the planning and training process. School-family relationships develop over time toward increasingly interactive relationships. The obligation of educational institutions, in accordance with the provisions of the regulations, is to invest families with shared educational responsibilities. The object of family-school relationships, the coaching of the younger generation, calls on adults from a community to share responsibility.